2020
DOI: 10.1002/hec.4210
|View full text |Cite
|
Sign up to set email alerts
|

Rolling back the gains: Maternal stress undermines pregnancy health after Flint's water switch

Abstract: Environmental disasters impact disadvantaged communities disproportionately both through the epidemiological challenge of exposure, but also by undermining the progress of public health efforts. This paper studies changes to smoking cessation, breastfeeding, and weight gain during pregnancy in the period following the switch in water supply in Flint, Michigan, in April 2014. As the switch resulted in immediate and significant deterioration in water quality, eventually leading to its contamination with lead, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Some studies also found that, among Flint residents, lower perceived tap water quality was associated with poorer mental and physical health and that the negative psychological consequences of the FWC continued even after the state of emergency was lifted. A recent causal study estimated a 11 percentage point increase in smoking and a 2% point decrease in breastfeeding among Flint mothers, resulting from stress related to the changes in water quality during the crisis ( 59 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also found that, among Flint residents, lower perceived tap water quality was associated with poorer mental and physical health and that the negative psychological consequences of the FWC continued even after the state of emergency was lifted. A recent causal study estimated a 11 percentage point increase in smoking and a 2% point decrease in breastfeeding among Flint mothers, resulting from stress related to the changes in water quality during the crisis ( 59 ).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of the literature studying SDWA has focused on non‐compliant drinking water. SDWA violations disproportionately impact minority and low‐income communities (Allaire et al., 2018; McDonald & Jones, 2018); egregious cases of water contamination, such as the case of Flint, have major community and health impacts (Christensen et al., 2023; Danagoulian et al., 2022; Danagoulian & Jenkins, 2021; D. S. Grossman & Slusky, 2019), and health‐based violations adversely impact infant health (Currie et al., 2013). Public reporting of these health‐based violations is an important mechanism to encourage compliance within the law (Baker et al., 2022; Bennear et al., 2009; Bennear & Olmstead, 2008; Grooms, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Deryugina and Molitor ( 2020 ) show that, in an unintended consequence of the displacement due to Hurricane Katrina, Medicare beneficiaries who moved to lower mortality areas experienced lower mortality rates after the disaster. Conversely, Danagoulian and Jenkins ( 2021 ) show maternal smoking and breastfeeding declined after the Flint water contamination. As preventive care makes up the plurality of dental care, 2 it serves as an effective area for evaluation of the impact of pandemic on preventive care more generally.…”
Section: Introductionmentioning
confidence: 99%